Pengembangan Koperasi melalui Pemantapan Manajemen Berbasis Syariah di KSPPS Keluarga Barokah Amanah (Karomah) Balongpanggang Gresik - Misbahul Khoir,; Minahul Mubin,; Khurun Imroatus Sholihah, (TAAWUN, 2021)
Cooperatives and Small and Micro Enterprises are one part of the entity that is the pillar of the people's economy. Problems in management at KSPPS Karomah are started from the low human resources and the weak application of discipline, both the discipline of members and managers of KSPPS Karomah. The purpose of this service is to realize the awareness of members to participate in having an active role in two things, namely realizing their roles and responsibilities as members, and for administrators and managers to be able to manage well and be able to provide service schemes with 5 (five) instruments. empowerment in the form of Alms (infaq), Loans, Financing, Savings and Time Investments. The method used for problem solving as the priority problems and urgent needs of cooperatives: Increasing the discipline of members and managers (Organization Stabilization, Management of KSPPS Karomah and Empowerment of Members). The results that can be achieved and the implementation of this service include: Increased management of KSPPS Karamah which is effective, efficient and professional, Standard Operating Procedures (SOP), SOM and organizational improvements, Increased network relations between members and administrators, supervisors and employees, Increased business income managed by KSPPS Karamah. The conclusions in this service include: improving database-based services, producing SOPs, SOM, National Service Journal with ISSN, promotion of the Karomah KSPPS Cooperative. Another additional output is the provision of an attendance machine, and a simple Excel application to measure the eligibility of members who apply for Sharia Savings, Loans and Financing at KSPPS Keluarga Barokah Amanah.